Inhibitors of type II transmembrane serine proteases in the treatment of diseases of the respiratory tract – A review of patent literature. (1st November 2020) - Murza, Alexandre; Dion, Sébastien P.; Boudreault, Pierre-Luc; Désilets, Antoine; Leduc, Richard; Marsault, Éric
ABSTRACT: Introduction: Type II transmembrane serine proteases (TTSPs) of the human respiratory tract generate high interest owing to their ability, among other roles, to cleave surface proteins of respiratory viruses. This step is critical in the viral invasion of coronaviruses, including SARS-CoV-2 responsible for COVID-19, but also influenza viruses and reoviruses. Accordingly, these cell surface enzymes constitute appealing therapeutic targets to develop host-based therapeutics against respiratory viral diseases. Additionally, their deregulated levels or activity has been described in non-viral diseases such as fibrosis, cancer, and osteoarthritis, making them potential targets in these indications Areas covered: Areas covered: This review includes WIPO-listed patents reporting small molecules and peptide-based inhibitors of type II transmembrane serine proteases of the respiratory tract. Expert opinion: Expert opinion: Several TTSPs of the respiratory tract represent attractive pharmacological targets in the treatment of respiratory infectious diseases (notably COVID-19 and influenza), but also against idiopathic pulmonary fibrosis and lung cancer. The current emphasis is primarily on TMPRSS2, matriptase, and hepsin, yet other TTSPs await validation. Compounds listed herein are predominantly peptidomimetic inhibitors, some with covalent reversible mechanisms of action and high potencies. Their selectivity profile, however, are often only partially characterized. Preclinical data are promising and warrant further advancement in the above diseases.